1999
DOI: 10.1083/jcb.144.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-induced Ca2+ Release in Chromaffin Cells Seen from inside the ER with Targeted Aequorin

Abstract: The presence and physiological role of Ca2+-induced Ca2+ release (CICR) in nonmuscle excitable cells has been investigated only indirectly through measurements of cytosolic [Ca2+] ([Ca2+]c). Using targeted aequorin, we have directly monitored [Ca2+] changes inside the ER ([Ca2+]ER) in bovine adrenal chromaffin cells. Ca2+ entry induced by cell depolarization triggered a transient Ca2+ release from the ER that was highly dependent on [Ca2+]ER and sensitized by low concentrations of caffeine. Caffeine-induced Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
206
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 173 publications
(214 citation statements)
references
References 66 publications
7
206
1
Order By: Relevance
“…Both cADPR and caffeine released also Ca 2+ from the secretory granules of insulin-secreting MIN6 cells [20], and caffeine, but not cADPR, released Ca 2+ from secretory granules in chromaffin cells [23]. The lack of effect of cADPR may reflect an insensitivity to this agonist of the ryanodine receptors in these cells, as cADPR was also unable to release Ca 2+ from the ER in chromaffin cells [7]. The novel agonist nicotinic acid adenine dinucleotidephosphate (NAADP) was also effective to release Ca 2+ from zymogen granules [69], platelet acidic stores [41], insulin-secreting MIN6 cells [70] and the acidic Ca 2+ stores of PC12 cells [71].…”
Section: Mechanisms Of Ca 2+ Release From the Secretory Granulesmentioning
confidence: 97%
See 2 more Smart Citations
“…Both cADPR and caffeine released also Ca 2+ from the secretory granules of insulin-secreting MIN6 cells [20], and caffeine, but not cADPR, released Ca 2+ from secretory granules in chromaffin cells [23]. The lack of effect of cADPR may reflect an insensitivity to this agonist of the ryanodine receptors in these cells, as cADPR was also unable to release Ca 2+ from the ER in chromaffin cells [7]. The novel agonist nicotinic acid adenine dinucleotidephosphate (NAADP) was also effective to release Ca 2+ from zymogen granules [69], platelet acidic stores [41], insulin-secreting MIN6 cells [70] and the acidic Ca 2+ stores of PC12 cells [71].…”
Section: Mechanisms Of Ca 2+ Release From the Secretory Granulesmentioning
confidence: 97%
“…Electron microscopy techniques have shown that the total calcium content of the ER from different cell types is in the range of 5-50 mM, with the highest values in the terminal cisternae of the sarcoplasmic reticulum and mean values of 5-10 mM [2,18], that is, 5-10-fold lower than in the secretory granules. The free [Ca 2+ ] in the ER has been also measured with low-Ca 2+ -affinity aequorin and is in the 500-800 M range [7], so that the Ca 2+ -bound/Ca 2+ -free relationship in the ER is about 10. In addition, the total calcium distribution in the ER is heterogeneous, with strongly positive cisternae (including the nuclear envelope) lying in the proximity of or even in direct continuity with other, apparently negative cisternae [13].…”
Section: The Problem Of the Free And Total Calcium Concentration In Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Uptake by SERCA increases exponentially with [Ca 2+ ] C and can reach maximal rates 70-80 μmol · l cells [3,55,60]. At the steady state, the ER fills to a level of 500-1,000 μM [Ca 2+ ].…”
Section: ]) the Ratio D[ T Ca]/d[camentioning
confidence: 99%
“…On the other hand, organelles interrupt physically the diffusion pathways and make them much longer and tortuous. In addition, many organelles avidly take up Ca 2+ and drain the Ca 2+ wave; on the contrary, other organelles amplify the [Ca 2+ ] C signal by releasing Ca 2+ [3,5,7,55]. In this way high [Ca 2+ ] C microdomains (HCMD) are built at the secretion site whereas [Ca 2+ ] C near the resting level is preserved at the cell core.…”
Section: Introductionmentioning
confidence: 99%